Intussusception as the initial presentation of previously undiagnosed Peutz–Jeghers Syndrome- A case report - kc, Sudeep; Poudyal, Himani (Birat Journal of Health Sciences, 2025)
Peutz-Jeghers Syndrome (PJS) is an autosomal dominant condition characterized by hamartomatous polyps within the gastrointestinal tract and mucocutaneous pigmentation. Patients with PJS have heightened risks for various malignancy, requiring regular follow up. This report discusses a 18-year-old male who initially presented to the Emergency Department with complaints of abdominal pain. Imaging and clinical findings were suggestive of PJS. This case report discusses a case of jejunal intussusception as a initial presentation in previosly undiagnosed PJS. Imaging is critical for diagnosis, identifying complications, and future surveillance.